TTX-resistant sodium channels functionally separate silent from polymodal C-nociceptors - Jonas, Robin; Prato, Vincenzo; Lechner, Stefan; Groen, Gerbrand; Obreja, Otilia; Werland, Fiona; Rukwied, Roman; Klusch, Andreas; Petersen, Marlen; Carr, Richard; Schmelz, Martin (Frontiers in cellular neuroscience, 2020)
Pronounced activity-dependent slowing of conduction has been used to characterize mechano-insensitive, “silent” nociceptors and might be due to high expression of NaV1.8 and could therefore be characterized by their tetrodotoxin resistance (TTX-r). Nociceptor-class specific differences in action potential characteristics were studied by (i) in-vitro calcium imaging in single porcine NGF responsive neurites, (ii) in-vivo extracellular recordings in functionally identified porcine silent nociceptors and (iii) in-vitro patch-clamp recordings from murine silent nociceptors, genetically defined by CHRNA3 (nicotinic acetylcholine receptor subunit alpha-3) expression. Porcine TTX-r neurites (n=26) in-vitro had more than twice as high calcium transients per action potential as compared to TTX-s neurites (n=18). In pig skin, silent nociceptors (n=14) characterized by pronounced activity-dependent slowing of conduction were found to be TTX-r, whereas polymodal nociceptors were TTX-s (n=12) and had only moderate slowing. Mechano-insensitive cold nociceptors were also TTX-r, but showed less activity-dependent slowing than polymodal nociceptors. Action potentials in murine silent nociceptors differed from putative polymodal nociceptors by longer duration and higher peak amplitudes. Longer duration AP in silent murine nociceptors linked to increased sodium load would be compatible with pronounced activity-dependent slowing in pig silent nociceptors and longer AP durations could be in line with increased calcium transients per action potential observed in-vitro in TTX-resistant NGF responsive porcine neurites. Even though there is no direct link between slowing and TTX-resistant channels, the results indicate that axons of silent nociceptors not only differ in their receptive, but also in their axonal properties.
Gesehen am 15.04.2020